2019
DOI: 10.28982/josam.518289
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety, depression, type D personality, somatosensory amplification levels and childhood traumas in patients with panic disorders

Abstract: How to cite / Atıf için: Taşdelen Y, Yağcı İ. Anxiety, depression, Type D personality, somatosensory amplification levels and childhood traumas in patients with panic disorders. This is an open access article distributed under the terms of the CreativeCommons Attribution-NonCommercial-NoDerivatives License 4.0 (CC BY-NC-ND 4.0) where it is permissible to download, share, remix, transform, and buildup the work provided it is properly cited. The work cannot be used commercially without permission from the journa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…The study results indicate that Type D individuals manifest both social and generalized anxiety [23]. Tasdelen and Yage [24] investigated depression, Type D personality, somatosensory amplification level, childhood trauma in panic disorder patients. The study concluded that individuals with panic disorder also show symptoms of depression, anxiety, and Type D childhood trauma.…”
Section: Discussionmentioning
confidence: 99%
“…The study results indicate that Type D individuals manifest both social and generalized anxiety [23]. Tasdelen and Yage [24] investigated depression, Type D personality, somatosensory amplification level, childhood trauma in panic disorder patients. The study concluded that individuals with panic disorder also show symptoms of depression, anxiety, and Type D childhood trauma.…”
Section: Discussionmentioning
confidence: 99%
“…Fourth, serum oxytocin levels may not reflect central oxytocin levels. Fifth, childhood trauma, attachment styles, genetic variations in oxytocin receptors that may affect oxytocin levels were not evaluated [54]. Sixth, oxytocin secretion changed situationally and during the daytime, but we measured serum oxytocin levels once and cortisol levels that affect oxytocin were not measured.…”
Section: Limitationsmentioning
confidence: 99%
“…Anxiety is a common emotional disorder among patients. There have been several studies related to anxiety for various types of diagnoses [3,4]. Since the 1970s, studies have been conducted on the level of knowledge on anesthesiologists and anesthesia applications, onto which research regarding patient satisfaction, measurement of preoperative anxiety and causes were added during later years [5][6][7].…”
Section: Introductionmentioning
confidence: 99%